Hemagglutinins from the green algae, Chlorophyta - Dinh Hung, Le; Thi Hoai Trinh, Phan (Vietnam Journal of Biotechnology, 2022)
The extracts from 30 species of the green algae were examined for hemagglutination activity with a variety of different animal and human erythrocytes which were untreated and treated with enzymes. Almost all extracts showed the activity at least toward one type of erythrocytes tested. Strong activity was detected in the extracts from 5 Chlorophyta species (Anadyomene plicata, Avrainvillea erecta, Boodlea struveoides, Halimeda velasquezii and Halimeda discoidea) with enzyme-treated rabbit and sheep erythrocytes. The hemagglutinins of some active species were examined for carbohydrate binding specificity, pH and temperature stability, and effect of divalent cation on their hemagglutination activities. All of the hemagglutinins had no affinity for monosaccharides, except hemagglutinin of Codium arabicum whose activities were inhibited by N-acetyl-D-galactosamine and N-acetyl-D-glucosamine. On the other hand, hemagglutination activities of the hemagglutinins were inhibited by some glycoproteins. The inhibition profiles with glycoproteins were different, depending on hemagglutininproducing species, and suggest the presence of lectins specific for high mannose N-glycans, complex N-glycans, or O-glycans. The hemagglutination activities of the green algal hemagglutinins were stable in a wide range of pH and temperature, and independent on divalent cations. Therefore, Vietnamese green algae may promise as a valuable source of new lectins for application.